La documentación electoral y el fichero histórico de diputados - García Muñoz, Montserrat (Revista General de Información y Documentación, 2002)
The Archive of Congress preserves the parliamentary documentation of the XIX and XX centuries. The electoral papers, which reflect the results of the political contest, enable the constitution of the House. The information they contain is assembled in a data base, The Historical Files of Congressmen, covering the period from 1810 to 1977.
Keywords: Constitution of Parliament; Parliamentarian